Profile of physiotherapists working with soccer teams in South Africa - Matthews Selomo; Maria E. Cochrane; Muhammad A. Dawood (South African Journal of Physiotherapy, 2023)
Background: Soccer is one of the fastest growing sports in South Africa and the number of physiotherapists working with soccer teams has increased significantly. Despite increased appointments, very little is known regarding the demographic, education and work profiles of these physiotherapists.